2017
DOI: 10.1159/000477206
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Analysis of a Biomarker Pool for Alzheimer Disease Risk in a North Indian Population

Abstract: Background: Alzheimer disease (AD) is a progressive neurodegenerative disease with a complex multifactorial etiology. Here, we aim to identify a biomarker pool comprised of genetic variants and blood biomarkers as predictor of AD risk. Methods: We performed a case-control study involving 108 cases and 159 non-demented healthy controls to examine the association of multiple biomarkers with AD risk. Results: The APOE genotyping revealed that ε4 allele frequency was significantly high (p value = 0.0001, OR = 2.66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…According to the very recent meta-analysis, which includes a total of 35 pieces of research: eighteen report an increase, fourteen show no change, and one reports a decrease in Cu level in the serum-plasma of this disorder [ 232 ]. Subsequently, three more studies have been published, stating increased Cu 2+ ions level in Alzheimer’s compared to that in the healthy controls [ 233 , 234 , 235 ].…”
Section: Contradictory Results About Copper Level In Admentioning
confidence: 99%
See 1 more Smart Citation
“…According to the very recent meta-analysis, which includes a total of 35 pieces of research: eighteen report an increase, fourteen show no change, and one reports a decrease in Cu level in the serum-plasma of this disorder [ 232 ]. Subsequently, three more studies have been published, stating increased Cu 2+ ions level in Alzheimer’s compared to that in the healthy controls [ 233 , 234 , 235 ].…”
Section: Contradictory Results About Copper Level In Admentioning
confidence: 99%
“…These recent researches have contributed considerably to the explanation of the previous controversy. In blood, a higher level of free plasma Cu, which has been identified in 50–60% of Alzheimer’s patients, can explain the higher level of serum Cu in AD [ 145 , 174 , 233 , 236 ]. Another earlier research also observed an increased concentration of serum copper ions in a special kind of AD (Alzheimer’s disease epsilon four apolipoprotein E allele carriers) [ 237 ].…”
Section: Contradictory Results About Copper Level In Admentioning
confidence: 99%
“…More specifically, the large stand most recent meta-analysis (total pool of subjects analyzed: 2128 AD vs. 2889 healthy controls) includes a total of 35 studies: 18 report an increase, 14 no difference, and one a decrease in values of copper in the serum–plasma in AD compared to healthy controls ( Li et al, 2017 ). Three additional studies appeared after the publication of this consensus result ( Guan et al, 2017 ; Pu et al, 2017 ; Talwar et al, 2017 ), reporting increased concentrations of Cu 2+ in AD patients vs. controls.…”
Section: Copper Ion Toxicity In Admentioning
confidence: 93%
“…Considering general circulation studies, two studies reported no overall differences in outcomes, while five studies show higher levels of copper in AD patients vs. controls (Table 1 ). Moreover, a recent meta-analysis ( 12 ) comparing 879 AD patients with 1712 controls has shown that the plasma copper component that circulates not bound to ceruloplasmin (non-Cp copper) is increased in AD, as confirmed by studies published after this publication ( 13 , 14 ).…”
mentioning
confidence: 82%